Factors of success of Polish managers under the systems transformation - Strzałecki, Andrzej; Tomaszewicz, Beata (Studia Psychologica: Theoria et praxis, 2004)
The senior author’s model of The Style of Creative Behavior (SCB) together with Strelau’s Regulative Theory of Temperament (RTT), Antonovsky’s model of the Sense of Coherence (SOC), and Guilford’s Structure-of-Intellect Model (SIM) were used to explain effective management under systems transformation in Poland. The multivariate analysis of variance (MANOVA) was used to test the differences between two groups of subjects: senior managers – criterion group (N=43), and civil servants – control group (N=43). The following instruments were used: “The Creative Behavior Questionnaire” (SCB), “The Formal Characteristic of Behavior–Temperament Inventory” (RTT), “Sense of Coherence Questionnaire” (SOC), and “Match Problems II” (Adaptive Flexibility of Thinking from SIM). The tests of between-subjects effects have reached significant level for all variables except that of Endurance, Perseverance, and Sensoric sensitivity from FCB-TI. The discriminant analysis carried out for all variables gave 87,2% of correct classification (Canonical correlation is equal 0,705). However, in the step-wise option two variables entered eventually: Adaptive flexibility of thinking (SIM), and Meaningfulness (SOC). This solution gave 80,2% correct classification, and canonical correlation is 0,656. The article ends with the discussion of personality, cognitive, and axiological determinants of the success of effective management, and the creativity syndrome of the work of Polish managers is stressed.